PUBLIC SEMINAR ON COVID-19 PREVENTION AMONG FAMILY CAREGIVERS OF HEMODIALYSIS PATIENTS - Zulkhair Ali; Novadian Novadian; Suprapti Suprapti; Herleni Kartika; Eddy Yuristo (Conferences of Medical Sciences Dies Natalis, 2021)
Covid-19 is usually severe and represents a poor outcome, particularly in patients who have underlying co-morbidities. Among end-stage renal disease patients dependent on dialysis, covid-19 was related to increased morbidity and mortality. There is no causative therapy currently for covid-19. Thus prevention is mainly the best attempt to limit the burden of the disease. The preventive measure may depend on vaccination and public behavior in controlling the spread of the SARS-CoV-2. In the setting of the dialysis center, the patients' and caregivers' compliance with preventive measures is critical in preventing the spreading of Covid-19. The individual's knowledge and attitudes of COVID-19 are likely to influence individual adherence. Evidence suggests that an individual’s knowledge is critical in combating pandemics. Current community service was aimed to increase family caregivers of dialysis patients’ knowledge on covid-19 prevention.